![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2^x.2^{x+3}=64^2:2^5\)
\(2^x.2^x.2^3=2^{12}:2^5\)
\(2^x.\left(1+8\right)=2^7\)
\(2^x.9=2^7\)
\(\Rightarrow x=\varnothing\)
\(2^{2x+3}=64^2:2^5\)
\(\Leftrightarrow2^{2x+3}=2^7\)
hay x=2
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(2\left(\dfrac{1}{2}x-\dfrac{1}{3}\right)-\dfrac{3}{2}=\dfrac{1}{4}\\ \Leftrightarrow2\left(\dfrac{1}{2}x-\dfrac{1}{3}\right)=\dfrac{7}{4}\\ \Leftrightarrow\dfrac{1}{2}x-\dfrac{1}{3}=\dfrac{7}{8}\\ \Leftrightarrow\dfrac{1}{2}x=\dfrac{29}{24}\\ \Leftrightarrow x=\dfrac{29}{12}\)
b. \(\dfrac{3}{4}-2\left(2x-\dfrac{2}{3}\right)=2\\ \Leftrightarrow2\left(2x-\dfrac{2}{3}\right)=-\dfrac{5}{4}\\ \Leftrightarrow2x-\dfrac{2}{3}=-\dfrac{5}{8}\\ \Leftrightarrow2x=\dfrac{1}{24}\\ \Leftrightarrow x=\dfrac{1}{48}\)
c. \(\left(2x-3\right)\left(6-2x\right)=0\\ \Rightarrow\left[{}\begin{matrix}2x-3=0\\6-2x=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3}{2}\\x=3\end{matrix}\right.\)
Vậy ..........
![](https://rs.olm.vn/images/avt/0.png?1311)
P(x) + Q(x)= ( x^5 - 2x^2 + 7x^4 - 9x^3 - 1/4x) + ( 5x^4 - x^5 + 4x^2 - 2x^3 - 1/4)
= x^5 - 2x^2 + 7x^4 - 9x^3 - 1/4x + 5x^4 - x^5 + 4x^2 - 2x^3 - 1/4
= ( x^5 - x^5 ) - ( 2x^2 + 4x^2) + ( 7x^4 + 5x^4) - ( 9x^3 - 2x^3) - 1/4x - 1/4
= 6x^2 + 12x^4 - 6x^3 - 1/4x - 1/4
P(x) - Q(x)= ( x^5 - 2x^2 + 7x^4 - 9x^3 -1/4x) - ( 5x^4 - x^5 + 4x^2 - 2x^3 -1/4)
= x^5 - 2x^2 + 7x^4 - 9x^3 - 1/4x - 5x^4 + x^5 - 4x^2 + 2x^3 + 1/4
= ( x^5 + x^5) - ( 2x^2 - 4x^2) + ( 7x^4 - 5x^4) - ( 9x^3 + 2x^3) - 1/4x + 1/4
= 2x^5 - (-2)x^2 + 2x^4 - 11x^3 - 1/4x + 1/4
P(x)=x^5+ 7x^4- 9x^3+ 2x^2-1/4x-0
Q(x)=(-x^5+5x^4- 2x^3+ 4x^2+0x-1/4
= 12x^4-11x^3+ 6x^2-1/4x-1/4
![](https://rs.olm.vn/images/avt/0.png?1311)
P(x) = x^5 - 2x^2 + 7x^4 - 9x^3 - 1/4x
=x5+7x4-9x3-2x2-1/4x
Q(x) = 5x^4 - x^5 + 4x^2 - 2x^3 - 1/4
=-x5+5x4-2x3+4x2-1/4
P(x)+Q(x)=x5+7x4-9x3-2x2-1/4x -x5+5x4-2x3+4x2-1/4
=x5-x5+7x4+5x4-9x3-2x3-2x2+4x2-1/4x-1/4
=12x4-11x3+2x2-1/4x-1/4
P(x)-Q(x)=x5+7x4-9x3-2x2-1/4x +x5-5x4+2x3-4x2+1/4
=x5+x5+7x4-5x4-9x3+2x3-2x2-4x2-1/4x-1/4
=2x5+2x4-7x3-6x2-1/4x-1/4
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{-2}{3}x+\frac{1}{5}=\frac{1}{10}\)
\(\Leftrightarrow\frac{-2}{3}x=\frac{1}{10}-\frac{1}{5}\)
\(\Leftrightarrow\frac{-2}{3}x=\frac{-1}{10}\)
\(\Leftrightarrow x=\frac{-1}{10}\div\frac{-2}{3}\)
\(\Leftrightarrow x=\frac{3}{20}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
2x - 23. 33 = 138
2x - 8 . 27 = 138
2x - 216 = 138
2x = 138 + 216
2x = 354
2x = 354 : 2
x = 177
vậy x = 177
( 6x - 34 ) . 73 = 3 . 74
( 6x - 81 ) . 343 = 3 . 2401
( 6x - 81 ) . 343 = 7203
6x - 81 = 7203 : 343
6x - 81 = 21
6x = 21 + 81
6x = 102
x = 102 : 6
x = 17
vậy x = 17